Outcomes of Patients Presenting with Mild Acute Respiratory Distress Syndrome: Insights from the LUNG SAFE Study. (February 2019) - Pham, Tài; Serpa Neto, Ary; Pelosi, Paolo; Laffey, John Gerard; De Haro, Candelaria; Lorente, Jose Angel; Bellani, Giacomo; Fan, Eddy; Brochard, Laurent Jean; Pesenti, Antonio; Schultz, Marcus Josephus; Artigas, Antonio; et al.
Editor's Perspective: What We Already Know about This Topic: Hospital mortality in acute respiratory distress syndrome is approximately 40%, but mortality and trajectory in "mild" acute respiratory distress syndrome (classified only since 2012) are unknown, and many cases are not detected What This Article Tells Us That Is New: Approximately 80% of cases of mild acute respiratory distress syndrome persist or worsen in the first week; in all cases, the mortality is substantial (30%) and is higher (37%) in those in whom the acute respiratory distress syndrome progresses Background: Patients with initial mild acute respiratory distress syndrome are often underrecognized and mistakenly considered to have low disease severity and favorable outcomes. They represent a relatively poorly characterized population that was only classified as having acute respiratory distress syndrome in the most recent definition. Our primary objective was to describe the natural course and the factors associated with worsening and mortality in this population. Methods: This study analyzed patients from the international prospective Large Observational Study to Understand the Global Impact of Severe Acute Respiratory Failure (LUNG SAFE) who had initial mild acute respiratory distress syndrome in the first day of inclusion. This study defined three groups based on the evolution of severity in the first week: "worsening" if moderate or severe acute respiratory distress syndrome criteria were met, "persisting" if mild acute respiratory distress syndrome criteria were the most severe category, and "improving" if patients did not fulfill acute respiratory distress syndrome criteria any more from day 2. Results: Among 580 patients with initial mild acute respiratory distress syndrome, 18% (103 of 580) continuously improved, 36% (210 of 580) had persisting mild acute respiratory distress syndrome, and 46% (267 of 580) worsened in the first week after acute respiratory distress syndrome onset. Global in-hospital mortality was 30% (172 of 576; specifically 10% [10 of 101], 30% [63 of 210], and 37% [99 of 265] for patients with improving, persisting, and worsening acute respiratory distress syndrome, respectively), and the median (interquartile range) duration of mechanical ventilation was 7 (4, 14) days (specifically 3 [2, 5], 7 [4, 14], and 11 [6, 18] days for patients with improving, persisting, and worsening acute respiratory distress syndrome, respectively). Admissions for trauma or pneumonia, higher nonpulmonary sequential organ failure assessment score, lower partial pressure of alveolar oxygen/fraction of inspired oxygen, and higher peak inspiratory pressure were independently associated with worsening. Conclusions: Most patients with initial mild acute respiratory distress syndrome continue to fulfill acute respiratory distress syndrome criteria in the first week, and nearly half worsen in severity. Their mortality is high, particularly in patients with worsening acute respiratory distress syndrome, emphasizing the need for close attention to this patient population. Abstract : Approximately 80% of cases of mild adult respiratory distress syndrome persist or worsen in the first week; in all cases, the mortality is substantial (30%) and is higher (37%) in those in whom the adult respiratory distress syndrome progresses.Supplemental Digital Content is available in the text.